Edukasi Pola Makan Ibu Hamil Untuk Mencegah Hipertensi Dalam Kehamilan Di Rw 06 Desa Sirnagalih - Munir, Rindasari; Az Zahra, Nanda; Rahmawati, Ayu; Amyra Luthfiyah, Nada; Nurania, Siti; Mulyadi, Yuniarti (Pusat Riset dan Inovasi Nasional, 2024)
WHO (World Health Organization) data show that AKI in developing countries is about 20 percent related to gestational hypertension due to lack of rest patterns and a good diet. Hypertension in pregnancy becomes the second category of causes of maternal death. The purpose of the devotion is to increase the knowledge of pregnant women about a healthy diet to prevent hypertension in pregnancy. The lecture method was used in this service by means of delivering material directly to pregnant women in RW 06 Sirnagalih Village, sampling with saturated sampling of 25 respondents. The results obtained a T value of -9,798.and p value = 0.000 (α < 0.05), which means that there is an educational influence of the pregnant woman's diet to prevent hypertension. Results obtained from the pretest and post test that there was an increase in participants' understanding of the pre test score of 1.08 and the post test score of 1.88. The conclusion is that it can improve the knowledge of pregnant women about diet to prevent hypetence in pregnancy in RW 06 Sirnagalih Village.